![(x + \frac{2}{5} y)^{3} - (x + \frac{2}{5} y)^{3} (x + \frac{2}{5} y)^{3} - (x + \frac{2}{5} y)^{3}](https://tex.z-dn.net/?f=%28x+%2B++%5Cfrac%7B2%7D%7B5%7D+y%29%5E%7B3%7D+++-+%28x+%2B++%5Cfrac%7B2%7D%7B5%7D+y%29%5E%7B3%7D+)
simplify the above equation....
Answers
Answered by
4
Answer:
HOPE THIS ANSWER WILL HELP YOU........
Mark as brainliest......
# jasleenlehri13........☺✌
Answered by
1
Answer:
In △ABC AB=AC
⇒∠B=∠C (Angles opposite to equal sides are equal)
Now using angle sum property
∠A+∠B+∠C=180
∘
⇒80
∘
+∠C+∠C=180
∘
⇒2∠C=180
∘
−80
∘
⇒∠C=
2
100
∘
=50
∘
now ∠C+∠x=180
∘
(Angles made on straight line (AC) are supplementary)
⇒50
∘
+∠x=180
∘
⇒∠x=180
∘
−50
∘
=130
∘
Similar questions